Growth volatility and resource curse: does financial development dampen the oil shocks? - Moradbeigi, Maryam; Law, Siong Hook (Elsevier, 2016)
We assess whether well-developed financial system can moderate the positive association between oil volatility and growth volatility. Using a core sample of 63 oil-producing countries over the period 2000–2010, the empirical analysis confirms a negative link between oil terms of trade volatility and growth volatility. In addition, we find evidence that financial development dampens the effect of oil terms of trade volatility.